Our Kingdom come - Zlatar, Zdenko, 1947- (Boulder)
xxi, 464 sayfa
Keywords: “Analyzes an attempt in the early 17th century to create a Kingdom of the Slavs, a large state in the Balkans inhabited by South Slavs. The study describes the movement's support and the impact of the Counter-Reformation on the Slavs at a time when the Ottoman Empire was falling into decline.” --